Вплив різних типів запальної реакції на морфологічні зміни слизової оболонки щічної ділянки порожнини рота у щурів з гастродуоденітом = Influence of different types inflammatory response to morphological changes mucosa of the buccal region oral rats with gastroduodenitis - V. I. Bondarchuk (Kazimierz Wielki University, 2016)
Bondarchuk V. I. Вплив різних типів запальної реакції на морфологічні зміни слизової оболонки щічної ділянки порожнини рота у щурів з гастродуоденітом = Influence of different types inflammatory response to morphological changes mucosa of the buccal region oral rats with gastroduodenitis. Journal of Education, Health and Sport. 2016;6(6):565-578. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56698 http://ojs.ukw.edu.pl/index.php/johs/article/view/3644   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.   УДК: 616.311-091.8-02:616.33/.342-002]-092.9   ВПЛИВ РІЗНИХ ТИПІВ ЗАПАЛЬНОЇ РЕАКЦІЇ НА МОРФОЛОГІЧНІ ЗМІНИ СЛИЗОВОЇ ОБОЛОНКИ ЩІЧНОЇ ДІЛЯНКИ ПОРОЖНИНИ РОТА У ЩУРІВ З ГАСТРОДУОДЕНІТОМ   В. І. Бондарчук   ДВНЗ "Тернопільський державний медичний університет ім. І. Я. Горбачевського МОЗ України", м. Тернопіль   Резюме На основі експериментального дослідження вивчено гістологічні зміни слизової оболонки щічної ділянки порожнини рота у тварин з гастродуоденітом при впливі різних типів запальної реакції. Виявлено пошкодження епітеліоцитів та їх дистрофія, дезорганізація сполучнотканинних елементів підслизового шару і явища фіброзу, розлади гемодинаміки та зміни судин кровоносного русла. При цьому, хоча такі зміни якісно були схожими в усіх досліджуваних групах, вбачалася залежність їх вираженості від типу запальної реакції. Найбільш значними вони були у тварин з гіперергічним типом запальної реакції, окрім того у цій досліджуваній групі спостерігалася і вогнищева запальна інфільтрація. У щурів з гіпоергічним типом запальної реакції поширеність патологічних змін була найменш вираженою, про що свідчила також менша відносна кількість ушкоджених епітеліоцитів. При нормо- та гіперергічних типах запальної реакції з плином часу патологічні зміни слизової оболонки щічної ділянки порожнини рота прогресували.   Ключові слова: гіпоергічний тип запальної реакціїї, нормоергічний тип запальної реакціїї, гіперергічний тип запальної реакціїї, гастродуоденіт, слизова оболонка щічної ділянки порожнини рота.   ВЛИЯНИЕ РАЗЛИЧНЫХ ТИПОВ ВОСПАЛИТЕЛЬНОЙ РЕАКЦИИ НА МОРФОЛОГИЧЕСКИЕ ИЗМЕНЕНИЯ СЛИЗИСТОЙ ОБОЛОЧКИ ЩЕЧНОЙ ОБЛАСТИ ПОЛОСТИ РТА У КРЫС С ГАСТРОДУОДЕНИТОМ   В. И. Бондарчук   ГВУЗ «Тернопольский государственный медицинский университет  им. И. Я. Горбачевского МЗ Украины»   Резюме На основе экспериментального исследования изучены гистологические изменения слизистой оболочки щечной области полости рта у животных с гастродуоденитом при воздействии различных типов воспалительной реакции. Обнаружено повреждение эпителиоцитов и их дистрофия, дезорганизация соединительнотканных элементов подслизистого слоя и явления фиброза, расстройства гемодинамики и изменения сосудов кровеносного русла. При этом, хотя такие изменения качественно похоже во всех исследуемых группах, усматривалась зависимость их выраженности от типа воспалительной реакции. Наиболее значительными они были у животных с гиперергическим типом воспалительной реакции, кроме того в этой исследуемой группе наблюдалась и очаговая воспалительная инфильтрация. У крыс с гипоергическим типом воспалительной реакции распространенность патологических изменений была наименее выраженной, о чем свидетельствовала также меньше относительное количество поврежденных эпителиоцитов. При нормо и гиперергических типах воспалительной реакции с течением времени патологические изменения слизистой оболочки щечной области полости рта прогрессировали.   Ключевые слова: гипоергический тип воспалительной реакции, нормоергический тип воспалительной реакции, гиперергический тип воспалительной реакции, гастродуоденит, слизистая оболочка щечной области полости рта.       INFLUENCE OF DIFFERENT TYPES inflammatory response to Morphological changes mucosa of the buccal region ORAL RATS WITH GASTRODUODENITIS   V. I. Bondarchuk   Ternopil State Medical University of Ministry of Health of Ukraine   Summary On the basis of experimental research studied the histological changes in the mucosa of the buccal area of the mouth in animals with gastroduodenitis under the influence of different types of inflammatory response.